2022
DOI: 10.18280/ijht.400503
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Production Effect on the Planar Solid Oxide Fuel Cell Overheating

Abstract: In this work, a steady-state three-dimensional model is employed to investigate the heat transfer phenomena in a Planar Solid Oxide Fuel Cell (P-SOFC) and determine the current density impact on the overheating of this fuel cell type. The thermoelectric characteristics of various components of the P-SOFC are provided from the standard materials: Ni-YSZ for the anode, YSZ for the electrolyte, La1-xSrxMnO3 for the cathode, and LaCrO3 for the interconnectors. The partial differential equations governing the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Since the entropy change of the H2/O2 reaction is negative, the Nernst voltage of H2/O2 fuel cells decreases with an increase in temperature of 0.84 mV/ºC (Çavuşoğlu 2006). There are other studies in the literature where it is observed that the fuel cell Nernst voltage decreases with increasing temperature (Arıç et al, 2019;Lyu et al, 2020;Outeiro et al, 2008;Riad et al, 2023;Sahli et al, 2017;Şefkat and Özel, 2018).…”
Section: Effect Of Lhv and Hhv Values On Nernst Voltagementioning
confidence: 96%
See 2 more Smart Citations
“…Since the entropy change of the H2/O2 reaction is negative, the Nernst voltage of H2/O2 fuel cells decreases with an increase in temperature of 0.84 mV/ºC (Çavuşoğlu 2006). There are other studies in the literature where it is observed that the fuel cell Nernst voltage decreases with increasing temperature (Arıç et al, 2019;Lyu et al, 2020;Outeiro et al, 2008;Riad et al, 2023;Sahli et al, 2017;Şefkat and Özel, 2018).…”
Section: Effect Of Lhv and Hhv Values On Nernst Voltagementioning
confidence: 96%
“…Therefore, it is expected that the Nernst voltage will increase as the mole ratio of oxygen at the cathode increases. In some studies in the literature, it has been stated that Nernst voltage is directly proportional to the oxygen-mole ratio (Sahli et al, 2017).…”
Section: Effect Of Oxygen Mole Ratio At the Cathode On The Nernst Vol...mentioning
confidence: 99%
See 1 more Smart Citation